Evaluating lean execution performance in Indian MSMEs using SEM and TOPSIS models. (2016) - Ravikumar, M.M.; Marimuthu, K.; Parthiban, P.; Zubar, H. Abdul
To meet competitive requirements and reduce costs, many manufacturers are turning to lean manufacturing techniques. Various problems are usually faced in the implementation of lean manufacturing in the Indian micro, small and medium enterprises. This paper investigates the implementation of the lean manufacturing concept in the MSME sector. In particular, it examines the extent to which lean manufacturing can be implemented given the various financial constraints encountered in the current economic environment of India. To this end, lean implementations were conducted and studied in six Indian MSMEs. The study was conducted using structural equation modelling (SEM). The software, LISREL was used for calculating the ranking factors using TOPSIS and FUZZY TOPSIS technologies. The study was conducted with a view to elucidating the methodology of lean manufacturing that was successful, besides supporting the basic hypotheses. The final solution proposed is a systematic method postulated to improve the productivity and performance of the manufacturing industry.